Diagnostic usefulness of pregnancy-associated plasma protein-A in suspected pulmonary embolism - Berk, Serdar; Tamer Dogan, Omer; Itir Aydemir, Eylem; Bingol, Asli; Levent Ozsahin, Sefa; Akkurt, Ibrahim (Multidisciplinary Respiratory Medicine, 2013)
Background: The role of biomarkers for prognostication and diagnosis of pulmonary embolism (PE) is increasing. It has been reported that pregnancy-associated plasma protein-A (PAPP-A) can be used as a proatherosclerotic marker. The present study was aimed to evaluate whether PAPP-A levels are helpful in the differential diagnosis of patients presenting with suspected PE. Methods: 53 consecutive patients evaluated for suspected PE were prospectively enrolled in the study. Serum PAPP-A levels were measured in the blood samples which were taken at admission. Multi-slice computed tomographic angiography was used to verify the diagnosis of PE. Results: PE was detected in 24 out of the 53 patients, while it was excluded in 29 patients by thorax multi-detector computerized tomography scan. No significant difference was detected in mean serum PAPP-A level between groups (5.72 ± 0.31 mg/L vs. 5.67 ± 0.06 mg/L, respectively). Conclusions: Serum PAPP-A level has no role in the evaluation for PE.